Subtotal glossectomy with conservation of the hyo-styloglossus unit (HSU): a new pivotal concept for preserving tongue function in extended glossectomy - Gazzini, Luca; Caselli, Arianna; Dallari, Virginia; Fazio, Enrico; Abousiam, Monir; Nebiaj, Aurel; Albi, Cecilia; Accorona, Remo; De Virgilio, Armando; Greco, Antonio; Calabrese, Luca (Frontiers in Surgery, 2024)
Objective The local spread of oral tongue squamous cell carcinoma (OTSCC) follows pathways of dissemination along areas of lesser resistance. In more advanced scenarios, the tumor can extend beyond the hemi-tongue of origin, by passing through the lingual septum and following the fibers of the transverse muscle. This can lead to the invasion of the contralateral extrinsic muscles, the first being the genioglossus and more laterally the hyoglossus. An anatomically guided surgical resection of the tumor can be planned to ensure both oncological safety and an acceptable functional outcome. This approach aims to preserve the hyo-styloglossus unit (HSU) whenever feasible. Methods Between January 2019 and November 2022, six patients received extended glossectomy Type B (EG Type B), with preservation of the HSU. Preliminary oncological results and functional results in terms of swallowing (FOIS score) and quality of life (MDADI) are presented. Results Five out of the six patients are alive and disease-free, while one patient died due to other causes. All patients who were candidates for an EG Type B underwent a swallowing assessment prior to surgery and followed daily postoperative swallowing training. At discharge, the patients continued swallowing training in an outpatient clinic. Five out of the six patients reached a full oral diet within 1 year of follow-up. Conclusion The oncological results confirm the safety of this technique. The importance of preserving the HSU, the minimal functional unit, shows very encouraging results in terms of swallowing rehabilitation.